ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT PETANI PLASMA ANGGOTA KKPA (KREDIT KOPERASI PRIMER KEPADA ANGGOTA) DI PT. SARI ADITYA LOKA 1 KABUPATEN MERANGIN PROVINSI JAMBI - Agustina; Damayanti, Yusma; Elwamendri, Elwamendri (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2018)
The main goals of this research are 1) to know the application of the partnership pattern on Kredit Koperasi Primer Anggota (KKPA) by PT. Sari Aditya Loka 1 for Plasma farmers in Merangin regency in Jambi Province, 2) to analyze the income from KKPA scheme plasma farmers in PT. Sari Aditya Loka 1 Merangin regency in Jambi Province. It has been held for 5 months from January to June 2015. The primary data such as the financial data and also technical field as well in PT. Sari Aditya Loka 1were taken by doing some interviews with respondents. The secondary data wascollected from related institutions such as Centre of Jambi Provincial Statistics (BPS), Jambi Plantation Department.The results of this research showed that the system of partnerships which applied by PT. Sari Aditya Loka 1 is KKPA system in which farmers are guided directly by the company through Cooperation’s Village Unit (KUD). Theincome received by plasma farmers in PT. Sari Aditya Loka 1 from 2014 to 2015 is Rp. 1.545.255,26/ Farmer / year.This was advised to the Company to improve the transportation and infrastructure facilities in order to expedite the oil palm process, especially in the transport of fresh fruit bunches (TBS), and also giving some trainings and guidiances to KUD staffs and farmer groups members which is hoped in partnership about the way of oil palm cultivation to the farmer group members so farmers could be active and independent in planting oil palm. Eventhough the age of old age group plantation income is already old, but it is still economicals